New Fields and Strings in Subnuclear Physics : Proceedings of the International School of Subnuclear Physics. - Zichichi, Antonino (Subnuclear series., 2002)
In August/September 2001, a group of 75 physicists from 51 laboratories in 15 countries met in Erice, Italy to participate in the 39th Course of the International School of Subnuclear Physics. This volume constitutes the proceedings of that meeting. It focuses on the theoretical and phenomenological developments in string theory, as well as in all the other sectors of subnuclear physics. In addition, experimental highlights are presented and discussed. Contents: Mini-Courses on Basics: Lattice QCD Results and Prospects (R D Kenway); Non-Perturbative String Theory (R H Dijkgraaf); Neutrinos (B.